The Changing Presentation of the American Indian Museums and Native Cultures - West, W. Richard (University of Washington Press, 2004)
In this book, which grew out of a landmark NMAI symposium in 1995, Native and non-Native scholars and museum professionals explore issues concerning the representation of Indians and their cultures by museums in North America. Traditional museum exhibitions of Native American art and culture often represented only the past, ignoring the living Native voice. Today, museums have begun to incorporate the Native perspective in their displays. Even more dramatic is the increasing number of Indian-run museums. These essays explore the relationships being forged between museums and Native communities to create new techniques for presenting Native American culture.